2002
DOI: 10.1002/pd.297
|View full text |Cite
|
Sign up to set email alerts
|

The variation of risk estimates through pregnancy in second trimester maternal serum screening for Down syndrome

Abstract: The variation of risk estimates in second trimester maternal serum screening for Down's syndrome has been shown to be considerable in quality control schemes, i.e. UKNEQAS. We studied the biological variation of risk estimates in 16 women through pregnancy. The maternal serum markers alpha-fetoprotein (AFP), human chorionic gonadotrophin (hCG), unconjugated estriol (uE3) and beta-hCG were determined six times during late first to late second trimester, and the associated likelihood ratios for Down syndrome wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…It has been reported that the risk estimate changes when the test is repeated in the same pregnancy (2,3). In this study, a difference in trisomy 21 risk between samples 1 and 2 was seen, but was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that the risk estimate changes when the test is repeated in the same pregnancy (2,3). In this study, a difference in trisomy 21 risk between samples 1 and 2 was seen, but was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Trisomy 21 risk estimates change throughout the same pregnancy when the risk is estimated repeatedly in the same individual and/or by different laboratories (2,3). Moreover, temporal changes in maternal biochemical markers of trisomy 21 have been shown across the first and second trimesters of pregnancy (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Although MacRae et al had previously reported that the contributions of likely analytical variations in hCG, AFP and uE3 determinations on the estimation of trisomy 21 are negligible [11] as well as many other articles emphasizing various conclusions on this subject, a consensus that the borderline cases are the most problematic is almost accepted by many authors [4,5,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…This has been made feasible with the use of modern automated analytical techniques and equipment in laboratories with high throughput screening and by employing standardized quality control procedures. Although MacRae et al had previously reported that the contributions of likely analytical variations in hCG, AFP and uE3 determinations on the estimation of trisomy 21 are negligible [11] as well as many other articles emphasizing various conclusions on this subject, a consensus that the borderline cases are the most problematic is almost accepted by many authors [4,5,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation